DRY MATTER PARTITIONING AND SOURCE-SINK RELATIONSHIP AS INFLUENCED BY FOLIAR SPRAYS IN GROUNDNUT - SHARMA, PUSHP; SARDANA , VIRENDER; KANDHOLA, SUKHVINDER SINGH (The Bioscan, 2013)
Metabolism in plant is regulated by the exogenous growth regulating substances/PGR’s which offer new avenues in combating environmental stresses ,improving quality and enhancing productivity. The effect of foliar application of growth regulating substances viz. indole acetic acid (IAA @ 5 and 7.5 ppm) followed by second spray of ethrel 25 ppm, sequential spray of mepiquat chloride @ 125 ppm and mepiquat chloride @ 125 ppm + ethrel 25 ppm were visualized in two cultivars of groundnut SG-99 (bunch type) and M-13 (spreading). The impact of the foliar spays were significant on source strength and dry matter partioning in the two cultivars. Dry matter of pods (PDM) increased with both the concentrations of IAA in SG-99 and all the foliar sprays except IAA @ 7.5 ppm + ethrel 25 ppm in M-13. Source-sink relationship enhanced with the application of IAA @ 5 ppm + ethrel 25 ppm in SG-99 while sequential spray of mepiquat chloride @ 125 ppm, mepiquat chloride @ 125 ppm + ethrel 25 ppm in M-13 at 60 DAS. Mean pod yield (33.1%), shelling percentage (9.9%), 100 seed weight (8.9%) and oil content (1.0%) were higher in bunch type cultivar SG-99 as compared with M-13. A comparable increase in pod yield was recorded with IAA @ 7.5 ppm + Ethrel 25 ppm in SG-99 (11.8%) and M-13 (11.1%).